2017
DOI: 10.1039/c7cp04009a
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study of conformations of beta-cyclodextrin and its eight derivatives in four different solvents

Abstract: Understanding the atomic level interactions and the resulting structural characteristics is required for developing beta-cyclodextrin (βCD) derivatives for pharmaceutical and other applications. The effect of four different solvents on the structures of the native βCD and its hydrophilic (methylated βCD; MEβCD and hydroxypropyl βCD; HPβCD) and hydrophobic derivatives (ethylated βCD; ETβCD) were explored using molecular dynamics (MD) simulations and solvation free energy calculations. The native βCD, 2-MEβCD, 6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…The R g representing the mass weighted scalar length of each atom from the center of mass of the molecule is used to measure the size and shape of a molecule. The parameter A 79,80 describing the averaged cavity area of bCD molecule (assumed as a circle area) is calculated from the distances between bCD's center and the group of atoms of each glucose unit using the following equation:…”
Section: Conformation Upon Complexationmentioning
confidence: 99%
“…The R g representing the mass weighted scalar length of each atom from the center of mass of the molecule is used to measure the size and shape of a molecule. The parameter A 79,80 describing the averaged cavity area of bCD molecule (assumed as a circle area) is calculated from the distances between bCD's center and the group of atoms of each glucose unit using the following equation:…”
Section: Conformation Upon Complexationmentioning
confidence: 99%
“…The eligibility of certain kinds of cyclodextrin to achieve the desired stability of the system in solution is determined by the structure of CD and guest API [13]. The thermodynamic effect described by Gibbs free energy of complex formation, as well as by entailed stability constant Ks, can be estimated by structure-based modeling with in silico methods [11,12,[14][15][16][17][18]. Application of theoretical approaches, considering a vast number of testable cyclodextrin derivatives, is an essential tool for streamlining experimental investigation.…”
Section: Introductionmentioning
confidence: 99%
“…[52] In contrastt ow hat is commonly assumed, the cyclodextrin cone is quite flexible, especially in protic solvents. [53] This is apparent from the tumbling of glucoside units,w hich bend outwards and distortt he conical shape and the hydrogen-bondingn etwork. [49] Indeed, our analysisr eveals thats pecifically the fucosylated glucoside units show enhancedr otation andi ncreased chair flexibility.T hese tilted states are not frequent, but are stable over several nanoseconds ( Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Since a recent comprehensive study of native CDs in water showed that structural and dynamic properties may differ depending on the choice of force field, two different force fields, that is, GROMOS 53A6 and Q4MD, were used in combination with the GROMACS simulation package . In contrast to what is commonly assumed, the cyclodextrin cone is quite flexible, especially in protic solvents …”
Section: Resultsmentioning
confidence: 99%